Congoville : Contemporary Artists Tracing Colonial Tracks. - Boons, Pieter; Colard, Sandrine; De Laet, Veerle; Colard, Sandrine; De Boeck, Filip; Kisukidi, Nadia Yala; De Roo, Bas; Middelheim, Antwerp (Leuven : Leuven Universitaire Pers, 2021)
Tayou, Pascale Marthine ; Kiwanga, Kapwani ; Mbikayi, Maurice ; Katambayi, Jean ; KinAct Collective ; Gbaguidi, Pélagie ; Rahmani, Zahia ; Willis Thomas, Hank ; Mahama, Ibrahim ; Benassi, Elisabeth ; Baloji, Sammy ; Augustijnen, Sven ; Leigh, Simone ; Ferreira, Ângela ; Isek Kingelez, Bodys
Congoville, Middelheim Museum, Antwerp, 29 May 2021 - 3 October 2021
boek